Tomography reconstruction of concrete materials for mesoscale modelling. Issue 7 (26th February 2020) - Mazzucco, Gianluca; Pomaro, Beatrice; Xotta, Giovanna; Maiorana, Carmelo E.; Salomoni, Valentina A.
Abstract : Purpose: The purpose of this paper is the numerical assessment of concrete behaviour close to failure, via the development of robust elastoplastic models inclusive of damage effects. If mesoscale investigations are to be considered, the model must take into account the local confinement effects because of the presence of aggregate inclusions in the cement paste and, correspondingly, the possibility to account for local 3D stress states even under uniaxial compression. Additionally, to enhance the predictive capabilities of a mesoscale representation, the reconstructed geometry must accurately follow the real one. Design/methodology/approach: The work provides a procedure that combines a 3D digital image technique with finite element (FE) modelling thus maintaining the original 3D morphology of the composite. Findings: The potentialities of the proposed approach are discussed, giving new insights to a FE modelling (FEM)-based approach applied together with a computer-aided design. Coupled mechanisms of mechanical mismatch and confinement, characterizing the combined cement matrix-aggregates effect, are captured and highlighted via the numerical tests. Originality/value: The novelty of this research work lies in the proposal of a digitally based methodology for a precise concrete reconstruction together with the adoption of an upgraded elastic–plastic damage model for the cement paste.